Pengaruh Video Health Education Terhadap Pengetahuan Perawatan Kaki Penderita Diabetes Mellitus Di Desa Cibolang Puskesmas Cibolangkidul - M. Shiddiq Rohmatulloh; Egi Mulyadi; Mustopa Saeful Alamsyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes Mellitus is a metabolic disease characterized by hyperglycemia resulting from abnormalities in insulin secretion, insulin action, or both. One of the complications of DM, such as diabetic foot ulcers, is chronic wounds below the ankle. This increases morbidity, mortality, and the quality of life of patients. Diabetic ulcers are often associated with a lack of knowledge among diabetic patients about foot care and skills in preventing worsening wounds. This lack of knowledge has been proven to be a contributing factor to why people with DM do not perform foot care independently. Therefore, providing education on diabetic foot care is necessary to prevent the increasing incidence of DM and to prevent diabetic ulcers. This study aims to determine the effect of video health education on the knowledge of foot care among diabetes mellitus patients in the Cibolang Village, the working area of Cibolangkidul Community Health Center. This is a quantitative study with a Quasi experimental research design using a one-group pretest-posttest design. Data collection was conducted using Non-Probability sampling technique, specifically purposive sampling. Based on the results of the Wilcoxon Signed Rank Test analysis, a P value of 0.001 < 0.05 was obtained, indicating that H0 is rejected and Ha is accepted. It can be concluded that there is an influence of video health education on the knowledge of foot care among diabetes mellitus patients in Cibolang Village, Cibolangkidul Community Health Center.